Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.02.21.960492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Survey for Selected Viral Pathogens in Wild Leopard Cats (Prionailurus bengalensis) in Taiwan with an Emphasis on the Spatial and Temporal Dynamics of Carnivore Protoparvovirus 1

Abstract: The leopard cat (Prionailurus bengalensis) has been listed as an endangered species under the Wildlife Conservation Act in Taiwan since 2009. In this study, we targeted viral pathogens, included carnivore protoparvovirus 1 (CPPV-1), feline leukemia virus (FeLV), feline immunodeficiency virus (FIV), coronavirus (CoV), and canine morbillivirus (CMV), using molecular screening. The spatial and temporal dynamics of the target pathogens were evaluated. Through sequencing and phylogenetic analysis, we aimed to clari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…FeLV infection often causes myelosuppressive lymphoma or viral immunosuppression; although no FeLV positivity (0%) was detected in this study, previous reports have shown the prevalence of the virus in domestic cats is as high as 70% (Suntz et al., 2010; Westman et al., 2019). Reports of FeLV prevalence in cat populations around the world are numerous (Chen et al., 2021), the high prevalence of FeLV in cats is closely linked to both endogenous and exogenous FeLV infection, and much research revealed that only the major domestic cat host and allied small cat species harbour endogenous FeLV (enFeLV) elements stably integrated into their genomes (Powers et al., 2018; Stewart et al., 2011), these enFeLV loads may have a significant impact on virus detection rates. Therefore, the high prevalence of FeLV in many areas most may be endogenous, and the infection rate of exogenous FeLV should be further tested.…”
Section: Discussionmentioning
confidence: 99%
“…FeLV infection often causes myelosuppressive lymphoma or viral immunosuppression; although no FeLV positivity (0%) was detected in this study, previous reports have shown the prevalence of the virus in domestic cats is as high as 70% (Suntz et al., 2010; Westman et al., 2019). Reports of FeLV prevalence in cat populations around the world are numerous (Chen et al., 2021), the high prevalence of FeLV in cats is closely linked to both endogenous and exogenous FeLV infection, and much research revealed that only the major domestic cat host and allied small cat species harbour endogenous FeLV (enFeLV) elements stably integrated into their genomes (Powers et al., 2018; Stewart et al., 2011), these enFeLV loads may have a significant impact on virus detection rates. Therefore, the high prevalence of FeLV in many areas most may be endogenous, and the infection rate of exogenous FeLV should be further tested.…”
Section: Discussionmentioning
confidence: 99%